Ci3T Leadership Team Members' Perceived Facilitators and Barriers to Implementation. Issue 6 (November 2022) - Royer, David James; Oakes, Wendy Peia; Briesch, Amy M.; Chafouleas, Sandra M.; Lane, Kathleen Lynne; Buckman, Mark Matthew; Sherod, Rebecca Lee; Common, Eric Alan
In this qualitative study we sought to understand the experiences of K-12 school personnel serving on Comprehensive, Integrated, Three-Tiered (Ci3T) leadership teams. We conducted 22 semi-structured interviews and five focus groups across three states and five school districts to determine team members' perceptions regarding facilitators and barriers to Ci3T implementation. We determined from common themes three priority areas for continued professional learning to support Ci3T implementation: (a) Ci3T onboarding and training for new team members, (b) communicating the vision of Ci3T to foster buy-in across stakeholders, and (c) providing Ci3T professional learning to faculty and staff. We discussed findings in terms of possible benefits to school leadership teams working within integrated tiered models and how results of this study may inform the creation of learning modules to support district and Ci3T leadership team members. We discuss limitations with future directions.